2006
DOI: 10.1016/j.profnurs.2006.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Gerontology Competencies Into Graduate Nursing Programs

Abstract: Abstract:Current demographic and health care utilization trends strongly indicate a rapidly increasing demand for nurses who are well qualified to care for older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…2007, Barakzai & Fraser 2008). Thus, it is not surprising that nurses are caring for older adults in most healthcare settings (Kennedy‐Malone et al. 2006, Denton & Spencer 2010, Canadian Institute of Health Information 2011), and educators are examining curricula to determine if there is adequate theoretical and clinical content to prepare nursing students for practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2007, Barakzai & Fraser 2008). Thus, it is not surprising that nurses are caring for older adults in most healthcare settings (Kennedy‐Malone et al. 2006, Denton & Spencer 2010, Canadian Institute of Health Information 2011), and educators are examining curricula to determine if there is adequate theoretical and clinical content to prepare nursing students for practice.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults are the fastest growing demographic world-wide [World Health Organization (WHO) 2007] and it is well understood that with increased age there is increased incidence of health challenges (Hickman et al 2007, Barakzai & Fraser 2008. Thus, it is not surprising that nurses are caring for older adults in most healthcare settings (Kennedy-Malone et al 2006, Denton & Spencer 2010 Institute of Health Information 2011), and educators are examining curricula to determine if there is adequate theoretical and clinical content to prepare nursing students for practice. Scholars around the world have identified that nursing education does not include the necessary content about older adult care (King 2004, Gilje et al 2007, Xiao et al 2008, Deschodt et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thornlow et al [11] identify that without a sufficient number of advanced practice nurses prepared in gerontology our nation is "woefully underprepared to address the complex health care needs of older adults" (p. 116). It is also significant to note that most nurses find themselves caring for older adults regardless of the care setting [12] .…”
Section: Preceptor Modelmentioning
confidence: 99%
“…Clearly, the initial step in community collaboration is for the nursing program to seek and develop strong relationships with community agencies, institutions, individuals and other essential resources as a part of establishing a strong network for educating advanced practice nurses and strengthening available services in the community. The creation of a network of excellence [12] benefits the greater community which shares in the provision of care to older adults. The successful development of partnerships within the community establishes mutual exchange and commitment, and provides an ongoing forum for collaborative learning among all stakeholders.…”
Section: Program Strategies To Enhance Community Collaborationmentioning
confidence: 99%
See 1 more Smart Citation